Study of the Effect of Openings Positions on the Seismic Performance of RC Shear Walls - ناصر, عصام; منصور, نزيه; خضور, علي (Latakia University Journal -Engineering Sciences Series, 2020)
This paper deal with a study of the seismic performance of RC shear walls models ,which contain openings on SAP2000, analyzed by nonlinear static PUSH-OVER analyses, and modeled by MULTI-SHELL LAYER ELEMENT method. All studied walls are above 10 stories in height with real openings’ dimensions, which meet the fundamental architectural demands (doors and windows), and positioned in different ways (side opening, one opening in the middle, two symmetrical openings, and shifted openings). Comparison is done to every solid shear wall with walls in the same dimensions which contain the aforementioned openings’ positions. The results show that the values of stresses in reinforcement and concrete decrease when the length of the wall increases, and roughly the same thing applies for basic shears and max moments. The walls with shifted openings also show a better seismic behavior in comparison to the other walls.